2015
DOI: 10.1186/s13071-015-0695-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of compliance with community-directed treatment with ivermectin for onchocerciasis control in Kabo area, southwestern Ethiopia

Abstract: BackgroundCompliance with annual ivermectin treatment is a major challenge in community-directed treatment with ivermectin (CDTI) implementation. There are individuals who do not comply with the annual mass treatment, which contributes to the continuity for disease transmission. Hence, ensuring high treatment coverage and sustained compliance should be given due emphasis in the control of onchocerciasis. The aim of this study was to determine CDTI compliance rate and predictors of compliance where the CDTI was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
(30 reference statements)
8
12
1
Order By: Relevance
“…Multivariable regression analysis revealed a strong association between CDTI program perception and adherence (adjusted for age, sex, location and duration of stay in the village), whereas the association between beliefs on onchocerciasis and ivermectin adherence was not significant in this study. These findings are consistent with those of recent authors who found that strong predictors of adherence were related to perception on CDTI program, especially perception of CDDs work [ 10 , 11 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Multivariable regression analysis revealed a strong association between CDTI program perception and adherence (adjusted for age, sex, location and duration of stay in the village), whereas the association between beliefs on onchocerciasis and ivermectin adherence was not significant in this study. These findings are consistent with those of recent authors who found that strong predictors of adherence were related to perception on CDTI program, especially perception of CDDs work [ 10 , 11 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…For instance in a zone of 50% of onchocerciasis prevalence, there are 50% of “healthy” people (but with high risk of developing the disease) who have to comply in a yearly treatment which is accompanied by constraints such as stop alcohol intake the day of treatment, and potential side effects including tiredness with resultant impact in their daily activities, knowing that alcohol consumption and fear of side effects are documented reasons for ivermectin avoidance [ 13 , 14 ]. More generally, the main factors associated with compliance to ivermectin found in the literature include non-modifiable characteristics like age and gender, and also modifiable factors such as perceived susceptibility to onchocerciasis, perception of program organization, social influence and support, and perceived benefits and risks of ivermectin [ 10 , 12 , 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Respondents socio-demographic characteristics in the study area In the present study the highest percentage of male (55 %) than female (45 %) was observed, which was in a good agreement with the results of various scholars in the country (Dana et al, 2015;Adugna et al, 2015;Fitsum et al, 2016). The result on educational level obtained in the current study indicated majorities (32.9 %) were attained primary education, which was also in line with the findings of Fitsum et al (2016).…”
Section: Discussionsupporting
confidence: 91%
“…The odd of ivermectin treatment adherence was 2.1 times more in individuals' perceived threat of contracting onchocerciasis as serous disease. This finding is compliment with other scholarly findings [16,22,23,25,28,32,33,36]. This might be attributed to the fact that if communities' vulnerability to onchocerciasis is anticipated to be high then the uptake of the CLTI program is also high.…”
Section: Discussionsupporting
confidence: 89%
“…Various theories and studies suggested that adherence to onchocerciasis treatment with ivermectin was associated with sex [21,22], ethnicity [21,23], age [21][22][23], length of stay [21,23], familiarity of community-directed drug distributer [23], fear of drug side effects [21], perceived needs of support for intake of ivermectin [22,23], perceived performance of community drug distributer [21,23,24], religion [22], education [22], risk perception to oncocerciasis [23], measuring height the best way to determine a person's treatment dose [24], educational level [25], and perceived effectiveness of onchocerciasis treatment with ivermectin [21,23].…”
Section: Introductionmentioning
confidence: 99%